ChemInform Abstract: High Thermoelectric Performance and Enhanced Mechanical Stability of p‐Type Ge1‐xSbxTe. Issue 1 (17th December 2015) - Perumal, Suresh; Roychowdhury, Subhajit; Negi, Devendra S.; Datta, Ranjan; Biswas, Kanishka
Abstract: Ge1‐x Sbx Te (x = 0—0.1) is prepared from the elements (evacuated quartz tubes, 1223 K, 6 h).